Muscle Cell and Tissue - Current Status of Research Field 2018
DOI: 10.5772/intechopen.75903
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Functional In Vitro Model that Recapitulates Human Muscle Disorders

Abstract: Here, we aim to address the increasing need for a suitable human muscle in vitro model in order to advance in the knowledge of muscle pathophysiology and test novel therapies for muscle disorders. Our model is based on a simple 2D culture method that yields highly mature human myotubes under optimized environmental conditions. Culture conditions that produced functional and contractile human myotubes with an extended lifetime consisted in extracellular matrix overlay and addition of several trophic factors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…Our group has recently found that mouse and human myotubes deficient for CAPN3 display decreased SERCA protein levels as well as impaired Ca 2+ reuptake into the SR [67,68]. Moreover, we also found reduced SERCA expression in muscle samples from LGMDR1 patients.…”
Section: Ca2+-mediated Pathogenic Mechanisms Involved In Capn3 Defmentioning
confidence: 55%
See 3 more Smart Citations
“…Our group has recently found that mouse and human myotubes deficient for CAPN3 display decreased SERCA protein levels as well as impaired Ca 2+ reuptake into the SR [67,68]. Moreover, we also found reduced SERCA expression in muscle samples from LGMDR1 patients.…”
Section: Ca2+-mediated Pathogenic Mechanisms Involved In Capn3 Defmentioning
confidence: 55%
“…Although to date, these mechanisms are not entirely understood, there is solid evidence indicating that CAPN3 is a multifunctional protein. Different studies performed in animal models and human samples have shown that CAPN3 deficiency is associated with different features in the skeletal muscle such as oxidative damage [65,66], Ca 2+ dysregulation [67,68], sarcomere disorganization [69], mitochondrial abnormalities [66,70,71,72], abnormal muscle adaptation [73,74], and impaired muscle regeneration [71], which together would lead to inflammation, necrosis, fibrosis, atrophy, and progressive muscle degeneration, characteristic of LGMDR1 (Figure 2 and Figure 3). Indeed, patients in the early stages of the disease present an increased concentration of serum creatine kinase (CK), which is an unspecific hallmark of muscle damage [55,75].…”
Section: Limb-girdle Muscular Dystrophy-recessivementioning
confidence: 99%
See 2 more Smart Citations
“…We used the non-radioactive cytotoxicity assay CytoTox 96 (Promega, Madison, WI, USA) following indications [ 38 ].…”
Section: Methodsmentioning
confidence: 99%